Evaluasi Dan Perbaikan User Experience Pada Aplikasi Mobile Muslimnesia Menggunakan Metode Usability Testing Dan User Experience Questionnaire (UEQ): Studi Kasus Pada PT. DOT INDONESIA - Alfi Rochmah Primasari; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Muslimnesia Mobile App is an application made to help Muslims living the Islamic lifestyle and is developed by PT. DOT Indonesia. The application has never undergone a UX evaluation and difficulties from user's perspective are yet to be discovered. This research is done with usability testing method based on its learnability, efficiency, and satisfaction aspects, to identify usability issues; and user experience questionnaire (UEQ) to measure usability level and user experience. Results on the initial evaluation by using UEQ shows the app is on the positive level and the benchmark is on the above average level for each of the scale (except for the stimulation and novelty scale that are on the good level), while the result in the usability testing for learnability aspect is good with 96% percentage. On efficiency and satisfaction aspect, tested by UEQ, resulted in average efficiency scale of 1420 and on a good level. Satisfaction aspect is a part of hedonic concept which covers the scale of stimulation and novelty. Stimulation scale has the average score of 1430 and novelty scale has the average score of 1140, both scales are on the good/positive level. There are 15 issues found and there are 17 recommendations for design improvement. Next evaluation done to the improved design shows improvement on each UEQ scale, with perspicuity scale improved quite significantly. On the UEQ benchmark, the improved design shows improvement from above average level to the good level on each scale (except for dependability scale which on the above average level and stimulation scale on the excellent level). On usability testing, learnability aspect scores 100% with 4% improvement, efficiency aspect with 6% improvement. Satisfaction aspect improved simulation scale for 12% and novelty scale for 17%.